Safety and efficacy of left-sided three-port laparoscopic gastric cancer surgery: a prospective observational study - Fang, Xuan; Li, Ziyang; Gao, Xiaopeng; Guo, Xin; Ji, Gang; Song, Yanyang; Wei, Jiangpeng (Frontiers in Oncology, 2025)
BackgroundWhile reduced-port laparoscopic gastrectomy(RPLG) has emerged as a minimally invasive alternative, its standardization and long-term efficacy remain underexplored. This study evaluates the comparative outcomes of three-port (TPLDG) versus five-port laparoscopic distal gastrectomy (FPLDG).MethodsThis prospective multicenter study enrolled 355 gastric cancer patients meeting selection criteria. Surgical procedures adhered to D2 lymphadenectomy guidelines, with TPLDG utilizing a left-sided approach without auxiliary ports. Primary endpoints included inflammatory markers, recovery parameters, and 3-year survival outcomes.ResultsThe operative outcomes showed comparable results between groups, with similar operative times [140(125,160) vs. 135(120,150) minutes, p=0.068)] and total lymph node retrieved [(22(19,27) vs. 22(18,27) nodes, p=0.696)]. Notably, the TPLDG group demonstrated significant recovery advantages, including earlier flatus [(2(2,3) vs.3(2,3) days, p<0.001)], shorter hospital stays [4(3,5) vs. 5.2(4.2,6.3) days, p<0.001)], and reduced inflammatory responses as evidenced by lower postoperative CRP [(48.2 ± 21.4) vs. (68.5 ± 25.6) mg/L, p<0.01)] and IL-6 levels [(82.3 ± 31.2) vs. (115.4 ± 38.5)pg/mL, p<0.01)]. Importantly, oncological outcomes remained equivalent between groups, with comparable 3-year disease-free survival (85.4% vs 85.8%, p=0.85) and overall survival rates (89.4% vs. 89.2%, p=0.70), which were consistently maintained across stage-stratified analyses.ConclusionTPLDG achieves comparable oncological outcomes to conventional FPLDG while offering significant advantages in postoperative recovery and inflammatory response reduction. The left-sided three-port technique represents a viable standardized approach for RPLG, particularly suited for D2 lymphadenectomy in Asian populations.